Prophylaxis of Venous Thromboembolism after Hospital Discharge in Internal Medicine: Findings from the Observational FADOI-NoTEVole Study - Squizzato, Alessandro; Agnelli, Giancarlo; Campanini, Mauro; Dentali, Francesco; Agnelli, Francesca; Bonizzoni, Erminio; Franco, Alessandro; Gallo, Andrea; Gussoni, Gualberto; Nitti, Cinzia; Triolo, Giuseppa; Valerio, Antonella; Ventrella, Francesco; Fontanella, Andrea; for the FADOI-NoTEVole Study Group (Thrombosis and Haemostasis, 2019)
Background and Aim Post-discharge prophylaxis for venous thromboembolism (VTE) is a challenging issue in patients hospitalised in Internal Medicine Units (IMUs). The aim of this study was to evaluate the frequency and the factors associated with post-discharge prophylaxis for VTE in IMUs.Methods Multi-centre, retrospective study including consecutive patients who were admitted for any cause and discharged from an IMU.Results Overall, 3,740 patients (mean age 74.1 ± 15.7 years) were included in the study at 38 IMUs in Italy. At discharge, the percentage of patients receiving pharmacological thromboprophylaxis was 16.0% (20.1% after excluding patients treated with anticoagulants for indications other than VTE prophylaxis). At multivariable analysis, history of ischaemic stroke, hypomobility ≥ 7 days, central venous catheter, ≥ 10 versus ≤ 5 days of hospital stay, use of corticosteroids, cancer, history of falls, availability of a caregiver, infections and age were significantly associated with thromboprophylaxis, while an inverse correlation was observed with concomitant anti-platelet drugs and platelet count < 70,000/mm3. Patients with a Padua Prediction Score ≥ 4 versus < 4 and with an IMPROVE bleeding score ≥ 7 versus < 7 more frequently received prophylaxis at discharge (31.2% vs. 10.6%, p < 0.0001, and 25.7% vs. 19.6%, p = 0.028, respectively).Conclusion In this study, one in five patients discharged from an Italian IMU received prophylaxis for VTE. The perceived thrombotic risk is significantly related to the use of prophylaxis.
Keywords: prophylaxis for venous thromboembolism; Internal Medicine Units; post-discharge prophylaxis; predictors